If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -12 = 4(3x + 4) + -4 Reorder the terms: -12 + 13x = 4(3x + 4) + -4 Reorder the terms: -12 + 13x = 4(4 + 3x) + -4 -12 + 13x = (4 * 4 + 3x * 4) + -4 -12 + 13x = (16 + 12x) + -4 Reorder the terms: -12 + 13x = 16 + -4 + 12x Combine like terms: 16 + -4 = 12 -12 + 13x = 12 + 12x Solving -12 + 13x = 12 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -12 + 13x + -12x = 12 + 12x + -12x Combine like terms: 13x + -12x = 1x -12 + 1x = 12 + 12x + -12x Combine like terms: 12x + -12x = 0 -12 + 1x = 12 + 0 -12 + 1x = 12 Add '12' to each side of the equation. -12 + 12 + 1x = 12 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = 12 + 12 1x = 12 + 12 Combine like terms: 12 + 12 = 24 1x = 24 Divide each side by '1'. x = 24 Simplifying x = 24
| -45+X=-27 | | -13=k-13+14k | | 5m-5=-25 | | x-.20x=338 | | 10x+40=4x+8 | | 45+X=-27 | | 8+10k-11k=0 | | x-.20x=512 | | (-30(-17))-(210(-3))= | | -36=-11n+8n | | 6y-60=42 | | 12=x-(-11) | | -36=k-13+14k | | 13p+6=32 | | sin^-1(3.2/4) | | 34=x+9+12 | | 11m+8=19 | | 0.3x-0.6=0.2x+7 | | -n-7=-16 | | 0=-13b+13b | | 9y^4+12y^2+1=0 | | -13z+13=26 | | -3(4n+6)=-6(n-8) | | .03x+.05(200-x)=9 | | 7m-25=-4 | | 2m+20=26 | | X^2-8x-4=-11 | | 3.3=1.5-0.4 | | x+4k=0 | | -18=x-5 | | -15x+25=-95 | | 9z-17=-35 |